Student Essay Assessment System in Islamic Education: The Use of Conventional Methods and Web-Based Application Assistance - Riky Supratama; Husna Nashihin; Henik Nur Indahsari; Dina Auliatil Wahyuni; Hanura Dewi Fadilah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2025)
This study aims to analyze the student essay assessment system in Islamic Religious Education, focusing on the use of conventional methods and web-based application support. A qualitative approach with a comparative study design was employed. Data were collected through interviews with Islamic Education teachers of Grade XI at SMKN Muhammadiyah 1 Yogyakarta, which utilizes the Broexam Unlock examination application. Teachers play a crucial role in enhancing assessment competencies, including preparing test materials, developing scoring rubrics, and conducting manual evaluations. The results indicate that the conventional essay assessment method presents weaknesses, such as requiring considerable time and effort due to manual corrections. Conversely, the use of web-based applications such as Exambro offers greater efficiency in time and workload, as the system automatically generates results after the exam. These findings highlight that technology utilization through web-based applications can serve as a strategic innovation to enhance the effectiveness of Islamic Religious Education assessment systems in the digital era.